Stunting dan Pencegahannya di Desa Pulau Balai, Kecamatan Pulau Banyak, Aceh Singkil - Desi Safitri; Fauzan Arif; Fitri Handayani; Mirna Juwita; Rahmad Efendi; Salwa Sabila (Universitas Batanghari Jambi, 2022)
Stunting ia a condition in a child`s growth where the growth is not in accordance with his age due to lack of nutritional intake in accordance with the dose and for a long period of time or also due to other causes such as early marriage. One of them is in Aceh Singkil district which was almost in the red category with a prevalence of 29.6 percent of stunting cases in 2021. This research is an observational study which was carried out in Pulau Balai Village, Pulau Banyak District, Aceh Singkil Regency, so students of KKN UIN SU held counseling about the dangers of early marriage to prevent stunting and also counseling to the community to explain about stunting due to the lack of public knowledge about it. The results achieved can provide an understanding to the public about the dangers of stunting, as well as the stunting problem that occurs in Pulau Balai Village and find out the causes and ways to prevent stunting so that stunting cases that occur in Pulau Balai Village can be prevented and not increased.